Economic Contests: Comparative Reward Schemes - O'Keeffe, Mary; Viscusi, W. Kip; Zeckhauser, Richard J. (Journal of Labor Economics, 1984)
Contests are situations in which an individual's reward depends on his performance relative to others. Students are graded on a curve; the candidate with the most votes gets the political office; the underling who performs best is promoted to the executive position. Contests are useful in dealing with indivisible rewards, reducing monitoring costs, and minimizing risks from common uncertainties. They are employed to sort potential participants and, once they have entered, to induce appropriate effort from them. With monitoring precision and prize spreads as potential choice variables, optimal contest structures are derived for fair and unfair contests among equal and unequal participants. The converse problems of climbing-low-ability individuals enter the contest designed for high-ability candidates-and slumming are shown to be manageable.